Changes in oxygenation and clinical outcomes with awake prone positioning in patients with suspected COVID-19 In Low-Resource settings: A retrospective cohort study (2023)
Introduction: This study aimed to describe the use of awake prone positioning (APP) and conventional oxygen therapy (COT) in patients with suspected coronavirus disease (COVID-19) and respiratory failure in a limited-resource setting. Methods: This was a retrospective cohort study of hospitalized patients aged ≥18 years old who were placed in an awake prone position due to hypoxemic respiratory failure and suspected COVID-19. The patients were selected from a tertiary center in Cartagena, Colombia, between March 1, 2020, and August 31, 2020. Demographic, clinical, and laboratory variables were collated, and all the variables were compared between the groups. Results: The median age of the participants was 63 (IQR, 48.8-73) years (survivors: 59 [IQR, 43.568] years vs. non-survivors: 70 [IQR, 63-78] years, P ≤.001). Of the 1470 patients admitted for respiratory symptoms, 732 (49.8%) were hospitalized for more than 24 h, and 212 patients developed respiratory failure and required COT and APP (overall hospital mortality, 34% [73/212]). The mean rank difference in PaO2/FiO2 before and after APP was higher in the survivors than in the non-survivors (201.1-252.6, mean rank difference =51.5, P=.001 vs. 134.1-172.4, mean rank difference=38.28, P=.24, respectively). Conclusion: While using COT in conjunction with APP can improve respiratory failure in patients with suspected COVID-19 in low-resource settings, persistent hypoxemia after APP can identify patients with higher mortality risk. More evidence is needed to establish the role of this strategy.